Pengaruh Kualitas Audit, Ukuran Perusahaan, Financial Distress dan Komisaris Independen terhadap Nilai Perusahaan - Yori Amalatisha; Windhy Puspitasari (Syntax Literate, 2023)
The purpose of this study is to provide empirical evidence of the effect of audit quality, firm size, Financial Distress, Independent Commissioner on the integrity of financial statements. Manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2021 as quantitative data from this study and obtained from the financial statements of manufacturing companies listed on the Indonesia Stock Exchange (IDX). The financial statements of manufacturing companies that went public during the 2017-2021 study period became the object of the research population. Purposive sampling. The expected results in this study concluded that audit quality has a positive effect on the integrity of financial statements, firm size has a positive effect on the integrity of financial statements, financial distress has no effect on the integrity of financial statements, and independent commissioners have a positive effect on the integrity of financial statements.